TEOREMA RESIDU DAN APLIKASINYA DALAM INTEGRAL TAK WAJAR - ATKURRAHMAN, MOH.; ZULFITNI, MUNIAR; PRADITA, DIYAH AYU RIZKI (E-Jurnal Matematika; Vol 11 No 1 (2022)DO - 10.24843/MTK.2022.v11.i01.p352, 2022)
In this study discusses about the solve of improper integral  uses ordinary step and the solve uses residu theorem. For the ordinary step is used the concept of integral and substitution integral, and the for the residu theorem is used the concept of a series from complex functions in complex areas. this study purpose for apply the residue theorem to improper integral of the real function. And know the proportion to calculate the integral value using the residue theorem and the ordinary steps, and applying the residu theorem in calculating improper integral of the real function that can't be done using the ordinary steps. Using concepts or approaches of complex function series thus produced the formula to calculate the improper integral of the real function. And the result of this study is that calculating unnatural integrals is easier and faster using the residue theorem than using the ordinary step. Not all the integral to the real function can be calculated using the ordinary steps therefore it can be used the residu theorem formula as an alternative.